2007
DOI: 10.1007/s11096-007-9181-4
|View full text |Cite
|
Sign up to set email alerts
|

Cost-of-illness study of severe haemophilia A and B in five French haemophilia treatment centres

Abstract: It suggests a higher consumption and cost of anti-haemophilic drugs among children when compared to adults. Haemophilia B patients did not consume significantly more than haemophilia A patients, whereas the consumption and cost for patients with or without inhibitors differed significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 14 publications
0
23
0
1
Order By: Relevance
“…Comparing mean and median costs, it is evident some of the high cost cases cause the mean cost to be significantly higher than the cost for a typical patient (77,78,82).…”
Section: Schramm Et Al Examined Costs Incurred By Patients In Both Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing mean and median costs, it is evident some of the high cost cases cause the mean cost to be significantly higher than the cost for a typical patient (77,78,82).…”
Section: Schramm Et Al Examined Costs Incurred By Patients In Both Pmentioning
confidence: 99%
“…The distribution of costs over different patients tends to be skewed with either a small proportion of patients accounting for a large proportion of resource utilisation (82,95,96) or particular subgroups of patients incurring higher costs. For example, haemophilia patients with HIV were four times as expensive to treat as HIV negative (85), and seropositive polyarthritis was five times more expensive to treat than persistent oligoarthritis both in total and direct cost estimates for JIA patients (96).…”
Section: Evidence and Policy Implicationsmentioning
confidence: 99%
“…The low consumption of clotting factor concentrate in these countries [6] arises from the economic constraints of accessing this high-cost treatment product. In developed countries, hospital records provide accurate treatment data and can be used for studies on haemophilia economics [7][8][9][10]. These data are important as they describe the impact of lack of subsidized services on treatment of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The number is even higher in individuals with inhibitors treated with immune tolerance therapy. [20][21][22] In addition to direct health care costs, studies have also shown considerable indirect costs related to hemophilia. 18 These indirect costs include individuals' and caregivers' lost productivity, caregivers' unpaid time costs, and hemophilic individuals' disability.…”
Section: Cost Of Care In Hemophiliamentioning
confidence: 99%